Assessment of the Quality of Maritime Transport Services between Poland and Sweden from the Perspective of Passengers – Research Project - Jagoda WLODARSKA; Jacek WINIARSKI (Communications of International Proceedings, 2023)
The objective of this article is to outline research plans for assessing the quality of services provided on ferries transporting passengers between Poland and Sweden. The article details the research design, which involves conducting a diagnostic survey in the form of a questionnaire. The questionnaire will contain questions related to various aspects of sea travel, including but not limited to, comfort, standard and optional services, travel duration, and safety. A crucial element of the research will be the selection of participants, with the number of respondents who use sea transport between Poland and Sweden being the primary aggregating determinant.
Keywords: Quality assessment; services; maritime transport; Poland; Sweden; passengers